2014
DOI: 10.1371/journal.pone.0100239
|View full text |Cite
|
Sign up to set email alerts
|

The PlA1/A2 Polymorphism of Glycoprotein IIIa as a Risk Factor for Stroke: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe PlA1/A2 polymorphism of glycoprotein IIIa (GPIIIa) has been reported to be associated with risk of stroke in some studies, although other studies suggest no such association. This meta-analysis and systematic review was conducted to investigate the hypothesis that carriage of the PlA2 allele is a risk factor for stroke.MethodsElectronic databases (MEDLINE and EMBASE) were searched for all articles evaluating carriage of the PlA2 allele and the incidence of stroke. Pooled odds ratios (ORs) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 72 publications
3
37
0
1
Order By: Relevance
“…It was shown by Floyd et al 27 that an expression of the PlA2 allele of glycoprotein IIIa has an impact on platelet function. In this work, we studied the platelet nanomechanics and compared the topology and Young's modulus of platelets derived from healthy individuals and patients with DVT who either carry or not PlA2 allele in GPIIb/IIIa gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown by Floyd et al 27 that an expression of the PlA2 allele of glycoprotein IIIa has an impact on platelet function. In this work, we studied the platelet nanomechanics and compared the topology and Young's modulus of platelets derived from healthy individuals and patients with DVT who either carry or not PlA2 allele in GPIIb/IIIa gene.…”
Section: Discussionmentioning
confidence: 99%
“…23 The carriage of PlA2 allele has been associated with an increased risk of myocardial infarction and stroke and was postulated as a risk factor for venous thromboembolism (VTE). [24][25][26][27][28] Platelets play an important role in the development of venous thrombosis, and along with slow blood flow and vein wall damage, they contribute to a hypercoagulable and prothrombotic state. The occurrence of multiple interacting risk factors is a precondition for VTE development.…”
Section: Introductionmentioning
confidence: 99%
“…Since the study of Weiss et al is the first study which has reported P1A2 polymorphism as a risk factor for MI, some studies in the literature have been shown inconsistent results. 9,13,21,22 Several studies demonstrated that the P1A2 polymorphism is a strongly associated with MI. [23][24][25] Rest of studies did not find any results to verify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, a recent meta-analysis study has shown the significant relationship between increased MI risk and PlA2 polymorphism risk under 45 years old male patients. 13 Individuals that have PlA2 allele eventually have overly active thrombin in their blood and shown to have increased levels of coagulations after microvascular injury in muscle tissue.…”
mentioning
confidence: 99%
“…Clinical pregnancy rate was approximately 17 % higher for the Gpllla-PIA1 homozygotes than that in the Gpllla-PIA2 carriers (56 versus 48 %, p = 0.010). This correlation probably has not been able to reach strict statistical significance due to the use of an unselected group of participants undergoing their first IVF cycle, despite their large number, and the simultaneous comparison of nine SNPs which decreased the power of the study due to the necessary Bonferroni correction.The Gpllla-PIA2 allele constitutes a significant risk factor for arterial thrombosis [7,8], and more recent studies show that probably it is positively associated with deep venous thrombosis, as well [9]. In a recent pilot study of 60 strictly selected women with unexplained recurrent IVF-ET failures excluding all cases with other known risk factors, we reported an increased occurrence of carriers of the Gpllla-PIA2 allele, Capsule In contrast to the inconclusive results yielded for most inherited thrombophilic factors, there is accumulating evidence that the PIA2 allele of the platelet glycoprotein IIIa gene is associated with increased risk of IVF implantation failure.…”
mentioning
confidence: 99%